2021
DOI: 10.1002/joa3.12501
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cardiac involvement in pulmonary sarcoidosis using high‐resolution Holter electrocardiogram

Abstract: Background Early detection of cardiac involvement in patients with sarcoidosis is important but currently unresolved. The aim of this study was to elucidate the utility of frequency domain microvolt T‐wave alternans (TWA), signal‐averaged ECG (SAECG), and heart rate turbulence (HRT) using 24‐hour Holter ECG for detecting cardiac involvement in patients with pulmonary sarcoidosis. Methods This study consisted of consecutive 40 pulmonary sarcoidosis patients (11 males, 62 ± 13 years) who underwent 24‐hour Holter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Autopsy studies of patients with sarcoidosis have found evidence of cardiac involvement in up to 69.1% of cases (6) Signal-averaged electrocardiography (SAECG) may also be useful for early detection of CS in patients without intraventricular conduction delay (26)(27)(28)(29)(30). SAECG can detect late potentials, which are low-amplitude, high-frequency signals at the terminal portion of the QRS, which reflect heterogeneous and fragmented activation of diseased ventricular myocardium (26,29).…”
Section: Screening Of Patients With Extracardiac Sarcoidosismentioning
confidence: 99%
“…Autopsy studies of patients with sarcoidosis have found evidence of cardiac involvement in up to 69.1% of cases (6) Signal-averaged electrocardiography (SAECG) may also be useful for early detection of CS in patients without intraventricular conduction delay (26)(27)(28)(29)(30). SAECG can detect late potentials, which are low-amplitude, high-frequency signals at the terminal portion of the QRS, which reflect heterogeneous and fragmented activation of diseased ventricular myocardium (26,29).…”
Section: Screening Of Patients With Extracardiac Sarcoidosismentioning
confidence: 99%